2021 International Conference on Artificial Intelligence and Smart Systems (ICAIS) 2021
DOI: 10.1109/icais50930.2021.9395784
|View full text |Cite
|
Sign up to set email alerts
|

Covid Detection from X-RAY and CT Scans using Transfer Learning – A Study

Abstract: CoronaVirus cases have reached 55.6 million (as of 19 th Nov 2020) out of which about 9 million cases are in India alone. Out of these 55.6 million people, nearly 1.34 million people have unfortunately lost their life which is about 3 % of the total cases. The disease has become quite a risky infection that has spread quickly across the world and has been announced as a Pandemic by the World Health Organization (WHO). As the greater part of the Covid patients show respiratory manifestations (basically Pneumoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In their work of detection of COVID-19 with CT images using hybrid complex shearlet scattering networks [11], Ren et al presented a hybrid framework in which a single model was constructed by combining the complex shearlet scattering transform (CSST) and a suitable convolutional neural network. The wide residual network is also implemented in this suggested hybrid model, which performs well on sparse and locally invariant images.…”
Section: Et Al Published "Automatic Detection Of Coronavirus (Covid-1...mentioning
confidence: 99%
“…In their work of detection of COVID-19 with CT images using hybrid complex shearlet scattering networks [11], Ren et al presented a hybrid framework in which a single model was constructed by combining the complex shearlet scattering transform (CSST) and a suitable convolutional neural network. The wide residual network is also implemented in this suggested hybrid model, which performs well on sparse and locally invariant images.…”
Section: Et Al Published "Automatic Detection Of Coronavirus (Covid-1...mentioning
confidence: 99%
“…DenseNet and its variants were utilized in a number of deep learning articles, including [31,49,54,56,62,119]. ResNet and its variants were also widely utilized, with articles [31,39,44,46,47,49,50,54,55,58,59,[66][67][68]97] mentioning them. Researchers that have employed image processing and feature extraction for COVID-19 detection can be found in the image processing section.…”
Section: Discussionmentioning
confidence: 99%
“…Sharma employed the CNN model with X-ray images in 2021 [65], but they also used VGG16 and VGG19 since they both produced superior accuracy of 0.97 compared to 0.94 for CNN, but their CNN model required less computational resources than VGG16 and VGG19. Kumar et al proposed [66] in 2021, in which they tested VGG16 and ResNet models for COVID-19 identification using CT scan and X-ray pictures, as well as CLAHE, U-Net, and CNN for image cropping and histogram equalisation. They discovered that VGG16 provided superior accuracy while ResNet was more dependable, resulting in an accuracy of 0.974 and an F1 score of 0.979.…”
Section: Methods For Deep Learning Techniquementioning
confidence: 99%
“…Transfer learning aims to solve problems in the target domain using the knowledge that has been learned in the relevant domain. Many representative transfer learning methods have been put into practical applications, covering areas including text classification [1][2][3][4][5], medicine [6][7][8][9], transportation [10][11][12], recommendation systems [13][14][15][16], etc. Previous studies have shown that the model trained using the original features directly for cross-domain text classification is not ideal.…”
Section: Abbreviationsmentioning
confidence: 99%